Short Telomere Length Is Related to Limitations in Physical Function in Elderly European Adults - Montiel Rojas, Diego; Nilsson, Andreas; Ponsot, Elodie; Brummer, Robert J.; Fairweather-Tait, Susan; Jennings, Amy; de Groot, Lisette C. P. G. M.; Berendsen, Agnes; Pietruszka, Barbara; Madej, Dawid; Caumon, Elodie; Meunier, Nathalie; et al. (Frontiers in Physiology, 2018)
The present study aims to explore the potential influence of leucocyte telomere length (LTL) on both a single indicator and a composite construct of physical functioning in a large European population of elderly men and women across diverse geographical locations. A total of 1,221 adults (65-79 yr) was recruited from five European countries within the framework of NU-AGE study. The physical functioning construct was based on the 36-item Short Form Health Survey. Handgrip strength was used as a single indicator of muscle function and LTL was assessed using quantitative real-time PCR. Women had significantly longer (p < 0.05) LTL than men. Participants in Poland had significantly shorter LTL than in the other study centers, whereas participants in the Netherlands had significantly longer LTL than most of the other centers (p < 0.01). An analysis of LTL as a continuous outcome against physical functioning by using linear models revealed inconsistent findings. In contrast, based on an analysis of contrasting telomere lengths (first vs fifth quintile of LTL), a significant odds ratio (OR) of 1.7 (95% CI: 1.1 – 2.6; p < 0.05) of having functional limitation was observed in those belonging to the first LTL quintile compared to the fifth. Interestingly, having the shortest LTL was still related to a higher likelihood of having physical limitation when compared to all remaining quintiles (OR: 1.5, 95% CI: 1.1 – 2.1; p < 0.05), even after adjustment by study center, age, sex, and overweight status. Collectively, our findings suggest that short LTL is an independent risk factor that accounts for functional decline in ageing European populations. The influence of LTL on functional limitation seems driven by the detrimental effect of having short telomeres rather than reflecting a linear dose-response relationship.